Who Are Belgrade’s Most Desired Allies? - Natasza Styczyńska (Ksiegarnia Akademicka Publishing, 2021)
Serbia presents itself as a country skillfully balancing between the European Union (EU), Russia, and Asia, trying to maintain good political and economic relations with the biggest players on the international arena. The Covid-19 pandemic and China’s media-publicized assistance to Serbia has affected the perception of which countries are seen as Belgrade’s true allies. At the same time, Serbia remains a EU candidate country (membership negotiations officially started in 2014) and the European Union is not only Serbian biggest trading partner, but also the biggest donor. The main aim of the article is to compare the distinctive meaning that EU membership and cooperation with non-EU countries (mainly China and Russia) has for Serbian political parties, taking into account that the Covid-19 pandemic and the ‘vaccine diplomacy’ influenced the Serbian public discourse and perception on who is the Belgrade’s most trustful partner.